Zwiastowanie Zachariaszowi i Maryi (Łk 1,5-38). Na tle starotestamentalnych schematów literackich - Ordon, Hubert (The Biblical Annals, 2017)
The subject of the author’s reflection is the annunciation to Zechariah and Mary (Luke 1,5-38) approached from the literary point of view. The author especially wants to establish, what relations there are between the structure of those events and some Old Testament literary patterns. Hence in the first part of the article the construction of the first and the second annunciations is presented, and at the same time it is stressed, that Luke has shown them in a similar way. The second part of the article is devoted to a discussion of two Old Testament literary patterns: the promise of having a child, and the calling, with a specification of the latter’s basic elements. It turns out that both these patterns can be reduced to the same items: contact with God, presentation of the task, difficulties in fulfilling the task, consolidation, and sign from God. The last fragment of the article points to and accounts for the fact, that Luke, working on 1,5-38, has used not only the Old Testament pattern of the promise of having a child, but also the pattern of calling, especially that of Moses (Exod. 3,1-12) and Gideon (Judg. 6,11-24).